PENGARUH GOOD GOVERNANCE, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEMERINTAH - Hidayat, Indra; Ritonga, Kirmizi; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted using a survey method to regional work units in the city of Dumai. This study aims to determine the empirical evidence of the influence of good governance, organizational culture and leadership style on the performance of the government. The population in this study is on education in the city of Dumai. Samples taken office amounted to 262 104 people by the number of respondents. The type of data used is primary data by using questionnaire method of data collection. The method of data analysis used in this study is multiple regression (multiple regression) with the help of SPSS software version 17:00 The results showed that the variables of good governance, organizational culture and leadership styles affect the performance of the government. Adjusted R square value is equal to 0.525 . This suggests that the effect of independent variables on the dependent 52.50 % and the rest is influenced by other variables that are not included in this study, while the remaining 47.50 % is explained by other variables not included in this study.Keywords : Good Governance , organizational culture , leadership style , the performance of the government.